Lightweight Wood-Based Wall: The Long-Time Evaluation of Heat-Air-Moisture Transport - Durica, Pavol; Juras, Peter; Staffenova, Daniela; Rybarik, Jan (Communications - Scientific Letters of the University of Zilina, 2016)
Five lightweight timber-frame wall sections with various thermal insulations and outdoor coating colors have been exposed to real outdoor boundary climate conditions since 2010. The indoor boundary conditions were set as constant. This article compares measured temperatures inside individual sections of the wall fragment to non-steady Heat-Air-Moisture (HAM) simulations in WUFI and ESP-r. The wall sections differ from each other in used thermal insulation: mineral wool, glass wool and hemp. Another difference is in color of outdoor surface: yellow, white and dark grey. Some wall compositions are equipped with vapor retarder. Each section has attached some thermal sensors.
Keywords: platform frame; wood; experiment; HAM; moisture; thermal conductivity